Field testing of the universal calibration function for determination of soil moisture with cosmic‐ray neutrons. Issue 6 (27th June 2014) - McJannet, David; Franz, Trenton; Hawdon, Aaron; Boadle, Dave; Baker, Brett; Almeida, Auro; Silberstein, Richard; Lambert, Trish; Desilets, Darin
Abstract The semitheoretical universal calibration function (UCF) for estimating soil moisture using cosmic‐ray neutron sensors was tested by comparing to field measurements made with the same neutron detector across a range of climates, soil, latitude, altitude, and biomass. There was a strong correlation between neutron intensity and the total amount of hydrogen at each site; however, the relationship differed from that predicted by the UCF. A linear fit to field measurements explained 99% of the observed variation and provides a robust empirical means to estimate soil moisture at other sites. It was concluded that measurement errors, neutron count corrections, and scaling to remove altitudinal and geomagnetic differences were unlikely to explain differences between observations and the UCF. The differences may be attributable to the representation of organic carbon, biomass or detector geometry in the neutron particle code, or to differences in the neutron energy levels being measured by the cosmic‐ray sensor and modeled using the particle code. The UCF was derived using simulations of epithermal neutrons; however, lower energy thermal neutrons may also be important. Using neutron transport code, we show the differences in response of thermal and epithermal neutrons to the relative size of the hydrogen pool. Including a thermal neutron component in addition to epithermal neutrons in a modified UCF provided a better match to field measurements; however, thermal neutron measurements are needed to confirm these results. A simpler generalized relationship for estimating soil moisture from neutron counts was also tested with encouraging results for low biomass sites.